Engendering earthquake response spectra for Dhaka region usable in dynamic analysis of structures - Islam, A.; Jameel, M.; Ahmad, Syed Ishtiaq; Salman, F.A.; Jumaat, Mohd Zamin (Sci. Res. Essays, 2011)
Structures are subjected to time varying-forces due to earthquakes which in turn produce timedependent displacements and stresses within the structures. From a design stance, only the maximum values of displacement and stress are of interest. For survival, the structure must withstand the peak value whenever that may occur. Therefore, knowing the peak values is of utmost important and this information is made available in the form of response spectra. In this study, effort has been made to generate response spectra which may be directly used in the dynamic analysis of structures in Dhaka. As there is a deficiency in apposite earthquake data at Bangladesh especially for Dhaka region, time history of Dhaka Earthquake was at first generated from recently occurred nearby earthquake. Consequently following detailed procedure response spectrum is developed. As response spectrum for a given earthquake is quite irregular and has a number of peaks and valleys, statistical approach has been adopted to construct a smoothed response spectrum to make it suitable for design. The engendered response spectrum has been evaluated with the well-known code specified response spectrum and introduces as acceptable. Therefore, the research reveals a design âresponse spectrumâ for Dhaka earthquake for the detail dynamic analysis ensuring as competent data for seismic design of structures.